Trigeminal Neuralgia as a Rare Complication of Idiopathic Intracranial Hypertension - Sarov-Riviere, Mariana; Ancelet, Claire; Nasser, Ghaidaa; Caroff, Jildaz; Aghakhani, Nozar; Denier, Christian (Case reports in neurology, 2025)
Introduction: Idiopathic intracranial hypertension (IIH) is a rare cause of chronic headaches. Usually, patients with IIH present headaches and papilledema with no focal neurological signs. Classical MRI findings feature characteristic signs, i.e., dilated perioptic nerves sheath and empty sella turcica. Rarely, cranial nerve palsies existed, especially abducens nerve palsy. Case Presentation: We reported herein another rare clinical feature of IIH: trigeminal neuralgia in association with meningocele. This 35-year-old obese woman initially presented with chronic headaches and papilledema. Cerebral MRI showed classical IIH findings. The CSF opening pressure was increased. A treatment coupling acetazolamide and iterative lumbar punctures led to the regression of papilledema, but headaches were difficult to control. Ten years later, while she was lost to follow up and treated with acetazolamide by her general practitioner, she developed extremely painful neuropathic pain in the left trigeminal nerve territory, in association with a recurrence of the chronic headaches. A new MRI showed new bilateral cavum trigeminal meningoceles, predominantly on the left side, associated with an atrophy of the cisternal segment of the left trigeminal nerve. Angio-CT showed transverse sinus stenosis, treated by stenting. After this treatment, IIH symptoms disappeared, while trigeminal neuralgia amplified: a surgical procedure led to its complete disappearance. Conclusion: To our knowledge, this is the first case reported of trigeminal neuralgia associated with meningocele formation in IIH. Our case illustrates the great efficacy of venous stenting in IIH, and one may wonder whether earlier stenting could have avoided the subsequent development of meningoceles and subsequent neuralgia.